The community structure of macrobenthos in Batang Lupar estuary - Nurul Azliza, Binti Mohd Asri (Universiti Malaysia Sarawak, UNIMAS, 2012)
A survey on the macrobenthos was carried out at 6 stations in Batang Lupar estuary, Sarawak. The aims of this study are to determine the community structure of macrobenthos which include species richness, species evenness and species diversity, to investigate the relationship between distributions of macrobenthos and environmental parameter and to establish the baseline data of macrobenthos research in Batang Lupar estuary. Fourteen taxa of macrobenthos were recorded and the five most abundant taxa were Order Eunicida, Nereis sp, Order Sternaspida, Oligachaeta, and Amphipoda. The macrobenthos found here are typical of the macrobenthos that can be found on the other part of estuary in Malaysia.